Correction: Hood, M.A., et al. Synthetic Strategies in the Preparation of Polymer/Inorganic Hybrid Nanoparticles. Materials 2014, 7, 4057–4087 - Materials Editorial Office (Materials, 2014)
In [1], several sentences were repeated three times on pages 4062, 4063 and 4065. In addition, many references were incorrect. The errors were introduced by the editorial office during the editing process. We apologize for this mistake and any inconvenience this may have caused to authors and readers. The corrected manuscript is given below.[...]